1999
DOI: 10.1068/a312033
|View full text |Cite
|
Sign up to set email alerts
|

Welfare as Work? The Potential of the UK Social Economy

Abstract: The authors provide a critical assessment of the emerging academic and policy consensus over the potential of local social economy initiatives to deliver social and economic regeneration. Drawing on material from 60 case studies in the United Kingdom, they examine three central claims made for the social economy: that it is empowering, economically sustainable, and capable of providing a real alternative to the 'mainstream' public and private sector economies. They argue that the empirical evidence offers only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 6 publications
0
49
0
1
Order By: Relevance
“…A gradual move from redistributive philanthropy to forms of market-action is also found in some early UK research (Amin et al 1999;Westall 2001). The efect was to raise the proile of social businesses as a policy option through joint action by governments and private charitable foundations or through partnerships with 'responsible' corporations.…”
Section: Conceptualising Social Enterprisementioning
confidence: 96%
“…A gradual move from redistributive philanthropy to forms of market-action is also found in some early UK research (Amin et al 1999;Westall 2001). The efect was to raise the proile of social businesses as a policy option through joint action by governments and private charitable foundations or through partnerships with 'responsible' corporations.…”
Section: Conceptualising Social Enterprisementioning
confidence: 96%
“…A number of potentially relevant references were identified by the search strategy (Clabots and Dolphin 1992, Evans and McGaha 1998, Amin et al 1999, Zaza et al 2001, Burton et al 2004, McDonald 2004. However, no relevant economic evaluation or costing study was found.…”
Section: Economics Of Engagement: the Quality Of The Evidencementioning
confidence: 99%
“…Second, they provide scope for innovative capacity building on the ground, which may be beyond the capabilities of local authorities (Turner and Martin, 2005). Thus in addition to delivering public services, they may have the potential to simultaneously support local regeneration and build social cohesion (Amin et al, 1999). However, at least two problems associated with using social economy organisations to deliver public services can be identified, and which are explored below.…”
Section: Implications For Policy and Practice: Community Engagement Amentioning
confidence: 99%
“…In line with these policy changes and as part of its modernisation agenda, the UK government has increasingly looked to the social economy -voluntary and community organisations -to become involved in public service delivery. Because, it is argued, these organisations are rooted in their communities, they have the capacity to provide solutions to social issues that meet the needs of local people, and provide the additional benefit of building social cohesion and social capital (Amin et al, 1999;Williams, 2003). These developments can be seen in the context of a broader 'Third Way' policy agenda (Giddens, 1998;, and fit neatly into the thinking that has been so influential within the New Labour government since 1997.…”
Section: Introductionmentioning
confidence: 99%